1977
DOI: 10.1042/bj1620659
|View full text |Cite
|
Sign up to set email alerts
|

Binding of bile acids by 100 000g supernatants from rat liver

Abstract: 1. The binding of glycocholic acid, chenodeoxycholic acid and lithocholic acid to rat liver 1000 000g supernatants was studied by equilibrium dialysis. 2. The binding characteristics of the bile acids suggest that the binding components are involved in bile acid transport. 3. When mixtures of [14C]lithocholic acid and liver supernatants were eluted from columns of Sephadex G-75, a prominent peak of [14C]lithocholic acid appeared with proteins of mol.wt. approx. 40000. A second, smaller, peak of [14C]lithocholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…about 40000 being gel-filtered through a Sephadex G-75 column of dimensions 2.6cm x 30cm (cf. Ockner & Manning, 1974;Strange et al, 1977). The sample contained 20nmol of protein in 2ml of buffer (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…about 40000 being gel-filtered through a Sephadex G-75 column of dimensions 2.6cm x 30cm (cf. Ockner & Manning, 1974;Strange et al, 1977). The sample contained 20nmol of protein in 2ml of buffer (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We have been using the technique to find out if tissues from certain teleosts contain proteins that. will bind long-chain fatty alcohols, so far with negative results (A. Bauermeister & J. R. Sargent, unpublished work), and we have also been puzzled by the fact that complexes with rather similar dissociation constants have markedly dissimilar capacities to survive gel filtration intact (Strange et al, 1977). We have therefore analysed a model of the process of zonal gel filtration, in an attempt to define what experimental conditions should be used and how tight the binding of protein to ligand has to be for the complex to emerge undissociated from the column.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…More recently the same authors [4] found two macromolecular species capable of binding lithocholic acid, one of mol. wt 40 000 and the other of mol.…”
Section: Characterization Of Cholic Acid-binding Proteinsmentioning
confidence: 98%
“…In addition, intracellular proteins capable of binding bile acids have been described. Strange et al [3,4] have shown that bile acids bind to proteins present in high speed supernatant fractions from rat liver. Thus the transport of bile acids shows similarities to the transport of other organic anions.…”
mentioning
confidence: 99%